Health Modeling — An Innovative Educational Program for the General Medicine Specialty - M. M. Litvinova; M. S. Khamidulina; T. M. Litvinova; Yu. A. Lutokhina; E. N. Dudnik; N. V. Kireeva; K. V. Ivashkin; B. A. Volel (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present the principles and distinctive features of the innovative educational program “Health Modeling” for the General Medicine specialty, aimed at refocusing medical training toward proactive health preservation and disease prevention.Key points. The “Health Modeling” profile was introduced in 2023 at Sechenov University in response to the need to shift the focus of physicians’ work from treating existing diseases to effectively preventing the development of pathologies. This approach aligns with the global healthcare strategy of maintaining population health and increasing the duration of healthy life. The program seeks to equip students with a comprehensive set of competencies for preserving patient and public health using the latest advances in medical science and technology. Distinctive features of the curriculum include interdisciplinary modules structured by organ systems and a spiral progression of content, early immersion of students into clinical practice from the first year, and the translation of cutting-edge scientific knowledge into education through hands-on laboratory practicums. In the senior years, the learning trajectory is individualized, and students acquire healthcare management skills through internships in federal and regional healthcare institutions. Sechenov University is the first in Russia to implement such an integrated, organ system-based curriculum within the General Medicine specialty.Conclusion. The “Health Modeling” educational program represents a significant step forward in modernizing medical education with an emphasis on preventive care. This model prepares a new generation of physicians oriented toward health preservation at both individual and population levels and should be of interest to medical educators and administrators seeking to update training programs in line with contemporary global health challenges.